Genes, environment and Alzheimer's disease - Lazarov, Orly; Tesco, Giuseppina; ScienceDirect eBooks (London, UK : Academic Press is an imprint of Elsevier, 2016)
This volume explores the interplay between genetic and environmental risk factors in the induction of cognitive decline and the development of dementia-related diseases such as Alzheimer's.
Low-Density Lipoprotein ReceptorsFunctions of APP; Neurogenesis: Embryonic and Adult; Neurite Outgrowth; Axonal Transport; Synaptic Formation and Function; Transcription Factor; Metal Binding/Redox; Does Agb (BHave a Function?; APP Knockout Mice; APP and AD; Disrupted Axonal Transport; Disrupted Neurogenesis; Altered APP Processing/Translocation; Altered Signal Transduction; References; 5 Molecular Pathways in Alzheimer's Disease and Cognitive Function: New Insights into Pathobiology of Tau; Introduction; Normal Production and Function of Tau; Pathogenic Tau; Tau-Mediated Neuronal Deficitss
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed March 9, 2016).
Includes bibliographical references at the end of each chapters and index.
Elsevier
Keywords: Alzheimer's disease; Alzheimer's disease -- Molecular aspects; Alzheimer's disease -- Genetic aspects; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Alzheimer's disease; Alzheimer's disease -- Genetic aspects; Alzheimer's disease -- Molecular aspects; Electronic books